Common Chicory Performance as Influenced by Iron Concentration in the Nutrient Solution - Cecílio Filho, Arthur Bernardes [UNESP]; Mendoza Cortez, Juan Waldir [UNESP]; de Sordi, Daniel [UNESP]; Urrestarazu, Miguel (Taylor & Francis, 2015)
An experiment was carried out from February 25 till April 10 of 2010 at the Jaboticabal campus of the Paulista State University (UNESP), state of São Paulo, Brazil, viewing to find out which would be the optimum and the phytotoxic levels of iron in the nutrients solution for common chicory (Cichorium intybus) plants. Iron concentrations in the nutrients solution were of 0.9, 2.7, 8.3, and 25 mg L−1. These treatments were replicated 4 times and the experimental units were distributed according to a randomized complete block design. The nutrient film hydroponic technique (NFT) was used. Growth parameters such as plant height and number of leaves as well as reproductive parameters such as green and dry mass production were evaluated. The optimal concentrations were found to be between 2.7 and 8.3 mg L−1 of iron in the nutrients solution. The concentration of 25 mg L−1 caused toxicity, although no visual sign of iron in excess was observed.
Keywords: Cichorium intybus; hydroponic; mineral nutrition of Fe; soilless culture